An archipelagic tourism development model: the case of Okinawa Prefecture. Issue 1 (2nd January 2017) - Nguyen, David N.
ABSTRACT: This paper advances geographic theoretical models on the spatial and temporal effects of tourism development and modifies them to analyze archipelagic destinations. Using Okinawa, Japan, as a case study, changes in the distribution of resort hotels, transportation linkages, tourism numbers, and development policies are examined over a period of 40 years. The results of this empirical study suggest that Okinawa's development corresponds very closely to the archipelagic model which, in turn, corresponds to other similar models predicting the spread of tourism.